Pengaruh Tinggi Tempat dan Tipe Tanaman Padi terhadap Keparahan Penyakit Hawar Pelepah - Nuryanto, B.; Priyatmojo, A.; Hadisutrisno, B. (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2014)
Sheath blight severity had been evaluated in the rice-producing centers of Central Java (along the road of Cilacap to Wonosobo) and Yogyakarta (along the road from Bantul to Sleman). Observations of the disease severity by survey method were conducted at farmersâ€™ fields. The objects of the observation areas were organized in a split plot design with 5 replications. The main plots were the elevation levels, grouped into three strata: 1) 0-200m, 2) 200-500m, and 3) 500-700m above sea level; the subplots were rice varietal types, which were separated into: 1) short type many tillers, 2) tall type with few tillers. The results showed that environment elevations and plant types of rice varieties significantly affected the disease severity. Compared to the lowland (0-200m), the high elevation environment (500-700m) decreased the disease severity around 25% at both Central Java and Yogyakarta, while compared with the short type many tiller rice varieties, the use of tall type few tiller rice varieties decreased the disease severity of around 10% in Central Java and in Yogyakarta. Increasing soil conductivity of about 1 milly Siemens/cm caused decreasing in disease severity up to 32.9%. Every 1 scale soil pH increase, caused a decrease in disease severity up to 2.4%. Ambient temperature increased by 1 Â°C caused the disease severity by 4.0% and an increase of 1% relative humidity lead to an increase of disease severity by 2.3%. In general, increases of soil conductivity and soil pH caused a decrease in disease severity, while increases in temperature and relative humidity of the environment under rice plant canopy resulted in the increase of disease severity.